2016
DOI: 10.1590/s0100-736x2016001000003
|View full text |Cite
|
Sign up to set email alerts
|

Intoxicação experimental por folhas de Crotalaria pallida (mucronata) em ovinos

Abstract: RESUMO: Descrevem-se o quadro clínico, patológico e o potencial tóxico das folhas verdes de Crotalaria pallida em ovinos. Para o experimento folhas verdes de C. pallida foram coletadas no município de São João do Sul em Santa Catarina e administradas por via oral para seis ovinos adultos, em doses únicas de 40, 20, 10, 5, 2,5 e 2,5g/kg, e para dois ovinos, em doses diárias de 0,63 e 1,25g/kg durante 30 dias. Reproduziu-se a intoxicação com doses letais a partir de 2,5g/kg. Um dos ovinos que recebeu a dose únic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…Acute clinical presentation of pulmonary edema was observed in sheep with gross and microscopic lesions restricted to the respiratory system. It was also found that non-lethal daily doses of C. pallida (0.63 and 1.25g/kg) given to sheep for 30 days did not have cumulative effect, as they did not become ill (Borelli et al 2016). It is worth noting that sheep are more resistant to PA than other species (Lucena et al 2010).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Acute clinical presentation of pulmonary edema was observed in sheep with gross and microscopic lesions restricted to the respiratory system. It was also found that non-lethal daily doses of C. pallida (0.63 and 1.25g/kg) given to sheep for 30 days did not have cumulative effect, as they did not become ill (Borelli et al 2016). It is worth noting that sheep are more resistant to PA than other species (Lucena et al 2010).…”
Section: Discussionmentioning
confidence: 90%
“…Pyrrolizidine alkaloid (PA) poisoning is a significant cause of mortality in Brazilian livestock (Lucena et al 2010). Spontaneous outbreaks of poisoning have been reported in cattle by the leaves and seeds of Crotalaria pallida (Lemos et al 1997), Crotalaria retusa (Nobre et al 2004b) and Crotalaria incana (Queiroz et al 2013); in sheep by C. retusa leaves (Dantas et al 2004, Riet-correa et al 2011) and seeds (Anjos et al 2010), and by C. pallida leaves (Borelli et al 2016); in horses by seeds of Crotalaria juncea (Nobre et al 1994) and C. retusa (Nobre et al 2004a); in donkeys by seeds of C. juncea and C. retusa (Pessoa et al 2013); in swine by Crotalaria spectabilis seeds (Ubiali et al 2011). Experimental poisoning has been reproduced in cattle with leaves of C. pallida (Tokarnia & Döbereiner 1982) and Crotalaria anagyroides (Tokarnia & Döbereiner 1983) and with C. pallida seeds (Boghossian et al 2007), and in swine with C. spectabilis seeds (Souza et al 1997, Torres et al 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Even before PA chemical structures were fully clarified, experiments were performed to confirm field observations (Pammel 2017) in studies that were soon reproduced in Brazil (Vandoni 1952;Torres 1954), associated with the beginning of the modernization of livestock in the country, from the middle of the XX century (Teixeira & Hespanhol 2014). In Brazil, the effects of Crotalaria species ingestion, accompanied by experimental studies, have been continuously documented for cattle (Boghossian et al 2007;Queiroz et al 2013), sheep (Nobre et al 2004;Sanchez et al 2013;Borelli et al 2016), pigs (Ubiali et al 2011), goats (Maia et al 2013), and horses (Nobre et al 2004). Poultry intoxication by seed ingestion is also common (Hatayde et al 1997).…”
Section: Resultsmentioning
confidence: 99%
“…The microscopic lesions observed in the lungs of sheep in this outbreak are compatible with those described in the outbreak in Rio Grande do Sul (Wouters et al 2013b), alterations such as proliferation of type II pneumocytes and formation of syncytial cells, which may be present in intoxication. In cases of Crotalaria pallida poisoning, clinical signs are characterized by increased respiratory rate and abdominal breathing, in addition to similar macroscopic lesions (Borelli et al 2016), can be considered differentials of T. micrantha poisoning. However, it is easily distinguishable under microscopy, in cases of C. pallida poisoning, the lesions are characterized by edema on the pleural surface, pleural spaces and around the peribronchial and peribronchiolar arteries (Borelli et al 2016) without involvement of the type II pneumocyte, characteristic of the current outbreak, which may contribute to the definitive laboratory diagnosis.…”
Section: Discussionmentioning
confidence: 99%